Experiences of faculty and staff nurses working with nursing students during clinical placement in residential aged care facilities: a systematic review of qualitative evidence. Issue 5 (7th May 2022) - McCloskey, Rose; Keeping-Burke, Lisa; Witherspoon, Richelle; Cook, Jessica; Morris, Patricia
ABSTRACT: Objective: The objective of this review was to synthesize evidence on the experiences of faculty and staff nurses working with nursing students in clinical placement in residential aged care facilities. Introduction: Nursing education helps prepare students to provide quality care to older adults. Nursing programs across the globe are championing the integration of content on the care of older adults into their curricula as well as recognizing the value of clinical placements that focus exclusively on this population. Staff nurses who work in residential aged care facilities often work alongside students. In this role, they can support faculty and mentor students. This review explored faculty and staff experiences of nursing student placements in such facilities. Inclusion criteria: This review considered qualitative studies that address the experiences of faculty and staff nurses working with nursing students in residential aged care facilities. Studies published in English from 1995 onward were included. Methods: The literature search was conducted in CINAHL, MEDLINE, Embase, and ERIC. The search for unpublished articles included Proquest Dissertations and Theses and Google searches of the Canadian Nurses Association and American Nurses Association websites. Papers were screened by two reviewers independently against the inclusion criteria. Those meeting the criteria were appraised using the JBI critical appraisal checklist for qualitative research. Key findings from included studies were extracted using a standardized tool and classified as unequivocal, credible, or not supported. This review followed the principles of meta-aggregration in line with the JBI approach. Results: Six studies, published between 2001 and 2017, were included in the review. A total of 32 findings were extracted and aggregated into nine categories. From the nine categories, four synthesized findings were developed: i) students enhance the environment, whereby faculty and staff perceive that student presence enhances the residential aged care work and living environment, ii) effort is required by faculty and staff to make the experience work, reflecting a need for faculty and staff to accept and work with negativities, iii) residential aged care facilities provide rich learning experiences, indicating an appreciation for available learning opportunities, and iv) importance of a residential aged care-academic partnership for a collaborative approach in creating positive experiences for faculty and staff working with students in this setting. Conclusion: Faculty and staff experiences highlight that residential aged care has the potential to provide students with valuable learning experiences, including how to provide comprehensive and quality nursing care to older adults. A lack of resources in residential aged care inspires faculty and staff to be creative in how they work with students. However, working with students can be challenging for faculty who lack interest and expertise in caring for older adults in this setting. Additionally, staff can become frustrated when they perceive that students do not value the learning opportunities that are available or do not appreciate the expertise required to work with older adults. Partnerships between residential aged care facilities and academic programs can ensure that faculty and staff have the support and resources required to optimize the clinical placements for students. Systematic review registration number: PROSPERO CRD42020168698